2012
DOI: 10.1007/s00284-012-0144-1
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Microbial Analysis of Ovine Rumen Fluid Incubated with 1,3,5-Trinitro-1,3,5-triazacyclohexane (RDX)

Abstract: In this study, the rumen was assessed for its potential to detoxify RDX using molecular microbial ecology as well as analytical chemistry techniques. Results indicated significant loss (P < 0.05) of RDX in <8-h post incubation, and qualitative LC-MS/MS analysis showed evidence for the formation of 1-NO-RDX (M-O + HCOO) and methylenedinitramine metabolites. A total of 1106 16S rRNA-V3 clones were sequenced, and most sequences associated with either the phyla Bacteroidetes or Firmicutes. A LibCompare analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…6% of the initial RDX remained. The rapid degradation of RDX by the ovine rumen microbiome is in agreement with previous observations [27]. The rumen microbiome was sampled for metagenomic analysis from four of the six time points tested (10, 60, 150 and 240 min).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…6% of the initial RDX remained. The rapid degradation of RDX by the ovine rumen microbiome is in agreement with previous observations [27]. The rumen microbiome was sampled for metagenomic analysis from four of the six time points tested (10, 60, 150 and 240 min).…”
Section: Resultssupporting
confidence: 88%
“…One possible explanation is that measurable changes in the microbial community composition or metabolic potential may take time to develop, and a four-hour incubation might not be sufficient to induce any changes. Significant changes induced by RDX in the number of sequences assigned to the genus Prevotella did not show up until eight-hour post-incubation in the rumen, when the substrate was no longer available [27]. However, the most likely explanation is that the RDX-degrading capacity of the ovine rumen microbiome is regulated at the transcriptional level.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although this family is not normally mentioned as being important for the bioremediation of recalcitrant pollutants, this and other published work support that idea. For example, in a study to assess the potential of rumen microbiome to detoxify hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX), an explosive that causes severe environmental contamination, it was concluded that members of the genus Prevotella were linked to its detoxification (Perumbakkam and Craig 2012). A study based on 16S rRNA gene libraries constructed using PCR primers for β-Proteobacteria to identify bacterial diversity in OMWW revealed that bacterial diversity in O. europaea var.…”
Section: Bacterial Communitiesmentioning
confidence: 99%